Migrants in Germany: Separate and Unequal - Olaf J. de Groot; Lutz Sager (Weekly Report, 2010)
Migrants of non-Western origin often live among themselves. This residential segregation is, however, not necessarily caused by a lacking will to integrate. It rather seems to a large part explainable with the socio-economic differences between population groups. The key to successful integration of migrants into the German society thus lies in the alleviation of inequalities in respect to education, income and German language skills.
Keywords: R0; J15; I32; 330; Segregation; Migration; Poverty